1998
DOI: 10.1038/1822
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the hyperthermophile chromosomal protein Sso7d bound to DNA

Abstract: Sso7d and Sac7d are two small (approximately 7,000 Mr), but abundant, chromosomal proteins from the hyperthermophilic archaeabacteria Sulfolobus solfataricus and S. acidocaldarius respectively. These proteins have high thermal, acid and chemical stability. They bind DNA without marked sequence preference and increase the Tm of DNA by approximately 40 degrees C. Sso7d in complex with GTAATTAC and GCGT(iU)CGC + GCGAACGC was crystallized in different crystal lattices and the crystal structures were solved at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
147
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(160 citation statements)
references
References 32 publications
(6 reference statements)
11
147
1
1
Order By: Relevance
“…We have compared the distance separating the tether attachment points for distal site disulfide crosslinking, namely the N 6 of adenine 5 and the ␤-carbon of residue 292, between the reported structures of hOGG1 that illuminate many of the base extrusion intermediates, from those that occur "early" to "late" in the pathway (Fig. 6A) (18,22,24,26). From this comparison we found that this distance varies as a function of progression along the nucleobase extrusion pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have compared the distance separating the tether attachment points for distal site disulfide crosslinking, namely the N 6 of adenine 5 and the ␤-carbon of residue 292, between the reported structures of hOGG1 that illuminate many of the base extrusion intermediates, from those that occur "early" to "late" in the pathway (Fig. 6A) (18,22,24,26). From this comparison we found that this distance varies as a function of progression along the nucleobase extrusion pathway.…”
Section: Resultsmentioning
confidence: 99%
“…When proteins interact with DNA lacking any specific recognition feature, the two macromolecules form large ensembles of rapidly interconverting complexes, and this inherent heterogeneity has hampered attempts to characterize nonspecific protein-DNA interactions at atomic resolution (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). We have overcome this problem by developing a straightforward means by which to drastically limit the region a protein can explore while diffusing along DNA, through the introduction of an intermolecular disulfide cross-link (DXL) between protein and DNA.…”
mentioning
confidence: 99%
“…Two structures of DNA-bound to Src homology 3 (SH3)-like folds are known (41)(42)(43). The proteins involved, Sso7d and Sac7d, bind in the minor groove of double-stranded DNA in a sequenceindependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we examined the photoreactions of 5-iodouracil ( I U)-containing 5Ј-d(GTAAT-I UAC)-3Ј and the Sso7d chromosomal protein from the hyperthermophilic archaeabacteria Sulfolobus solfataricus (8,9) and demonstrated that the uracil-5-yl radical abstracts hydrogen from the methyl group of T 5 at the sharp kink (16).…”
Section: Resultsmentioning
confidence: 99%